Out-of-pocket expenditure on dental services by elderly in Mexico - Alba-Castro, Marcela; Cigarroa, Igor; Pavón-León, Patricia (Horizonte Sanitario, 2024)
Objective: To determine the out-of-pocket expenditure on dental services (OOPE) and the factors associated with in, by elderly in Mexico. Materials and method: Cross-sectional study. We used data from ENIGH 2020 of the 32 states of Mexico. A database was constructed, and non-parametric tests and the Tobit regression model were applied to show the variables that had an effect on OOPE. Results: 17,280,412 (13,6%) were elderly. The OOPE was US 325,04 (quarterly). These expenses were for payment of dental consultations and rehabilitation treatments (dental prostheses, crowns). The associated factors were; marital status [married (US 7,31 IC: 0,89-13,72 p=0.03) and widowed (US 7,323 IC: 3,05-11,587 p=0.001)]; socioeconomic status [A/B+ (US 29,409 IC: 9,78-49,03 p=0.003), C+ (US 19,479 IC: 4,614-34,344 p= 0.010) and C (US 25,736 IC: 6,393-45,079 p=0.009)] and quarterly income by retirement and retirement pension (p=0.010). Conclusions: The dental services public health institutions offer, do not cover the necessary treatments to solve elderly oral problems. As a result, they need to assist the private services, which generates OOPE and affects more to elderly with lower socioeconomic status and income. The lack of care, contributes to the deterioration of health conditions, not allowing teeth to fulfill their functions, which do not improve the quality of life, essentially oral health-related quality of life. Keywords: Out-of-pocket; Direct expenditure; Health expenditure; Elderly; Public health services.